2020
DOI: 10.1002/lary.28712
|View full text |Cite
|
Sign up to set email alerts
|

Laryngotracheal Mucosal Surface Expression of Candidate Biomarkers in Idiopathic Subglottic Stenosis

Abstract: Objectives Idiopathic subglottic stenosis (iSGS) is an inflammatory process leading to fibrosis and narrowing of the laryngotracheal airway. There is variability in patient response to surgical intervention, but the mechanisms underlying this variability are unknown. In this pilot study, we measure expression of candidate targets at the mucosal surface of the subglottis in iSGS patients. We aim to identify putative biomarkers for iSGS that provide insights into the molecular basis of disease progression, yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The authors identified patterns of hypermethylation found in iSGS patients that may be associated with differential protein expression and suggest the possibility of iSGS subgroups [23]. Liu et al has demonstrated increased levels of CCL2, IFNγ, and IL-6 protein in iSGS specimen, although with marked heterogeneity [24]. Inflammation and cytokines (such as IL-17A) play an important role in stenosis [25].…”
Section: Idiopathic Sgsmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors identified patterns of hypermethylation found in iSGS patients that may be associated with differential protein expression and suggest the possibility of iSGS subgroups [23]. Liu et al has demonstrated increased levels of CCL2, IFNγ, and IL-6 protein in iSGS specimen, although with marked heterogeneity [24]. Inflammation and cytokines (such as IL-17A) play an important role in stenosis [25].…”
Section: Idiopathic Sgsmentioning
confidence: 98%
“…Patients who are tracheotomized due to iSGS have the lowest rate of decannulation (63%) [75•]. Recent research has built upon our knowledge of fibrogenesis in iSGS, but studies have yet to identify biomarkers to monitor disease progression and prognosis [24]. The IL-23/IL-17A inflammatory axis appears to be a potential therapeutic target [21].…”
Section: Idiopathic Sgsmentioning
confidence: 99%
“…All C57BL/6 mice were housed in a temperature-controlled specificpathogen-free facility under 12-hour light/dark cycles. Laryngotracheal complex (LTC) transfer was done as previously described (8). Briefly, LTC transplants were performed using donor tracheal segments from 8-week-old, 20-to 25-g female C57BL/6 mice (Jackson Laboratories, Bar Harbor, Maine).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Over the past decade, researchers and clinicians have started to shed light on the pathogenesis of SGS. In addition to histological evidence of exuberant granulation tissue and accumulation of permanent scar tissue, prior studies have shown an increased in several markers of inflammation and fibrosis, such as Interleukin (IL)-1, transforming growth factor beta (TGF-b), platelet-derived growth factor (PDGF), Interferon gamma (IFNG), as well as prostaglandin (PG)-2 from excised stenotic tissues (4)(5)(6)(7)(8). The importance of the immune system in the development of SGS was further emphasized by findings that immunodeficient mice failed to develop SGS (9), and that human subglottic tissues were significantly enriched for CD8+ resident memory T cells (10) as well as CD4+ T cells with increased expression of PD-1 and PD-L1 (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Although adjuvant medical therapies have more recently been employed including serial steroid injections, proton pump inhibitors, and inhaled corticosteroids, their efficacy remains inconsistent 5,8 . Heterogeneity in patient response to surgical and medical treatments underscores the need to better understand the pathogenesis of iSGS 5,9 . An improved understanding of the underlying mechanisms driving fibrosis in iSGS could deliver more effective and targeted therapies.…”
Section: Introductionmentioning
confidence: 99%